Transforming Biology Learning Through Project-Oriented Problem-Based Learning: Effects on Creative Thinking and Collaboative Skills - Arini Rahma Dhani (ANTHOR: Education and Learning Journal, 2026)
Creative and collaborative thinking skills are essential competencies that students must possess to meet the demands of 21st-century learning. However, these skills have not yet developed optimally because the learning process often focuses on conceptual mastery and fails to provide students with sufficient opportunities to actively solve problems and work together in teams. This study aims to analyze the effect of implementing the Project-Oriented Problem-Based Learning (POPBL) model on students’ creative and collaborative thinking skills in biology learning. This study uses a quasi-experimental method with a pretest-posttest non-equivalent control group design. Creative thinking skills were measured using a creative thinking essay test, and collaboration was measured using a collaboration skills questionnaire. The research sample consisted of students in the Biology Education Study Program who were divided into an experimental class and a control class. The data were analyzed using an Analysis of Covariance (ANCOVA) test after meeting the prerequisites of normality and homogeneity. The results of the study indicate that there is a significant difference between the experimental and control classes in terms of both creative and collaborative thinking skills. Students who learned using the POPBL model achieved higher results compared to students who followed conventional learning. Thus, the implementation of the POPBL model is effective in improving students’ creative and collaborative thinking skills.